US practitioner prescribing practices and patient characteristics of those newly treated with a buprenorphine transdermal patch system. (August 2014) - Pergolizzi, Joseph V.; Ben-Joseph, Rami; Chang, Chun-Lan; Hess, Gregory
Abstract Objectives: Medication prescribing information provides guidance to healthcare providers on how to prescribe a drug properly. Oftentimes patient factors in addition to the prescribing information are considered when selecting medications. Utilizing real-world pharmacy and medical claims data, this study assessed US practitioner prescribing practices of US approved transdermal buprenorphine system (BTDS) in relation to BTDS's full prescribing information (FPI) as well as the relationship between patient factors and initial BTDS dose. Research design and methods: Patients aged ≥18 years initiating BTDS between 1 January 2011 and 30 November 2011 were identified in the IMS Pharmacy and Private Practitioner Medical Claims databases. The index date was defined as the first filled BTDS prescription. Demographics, chronic pain-related medical conditions in the 12 months pre-index and prior medication use in the 6 months pre-index were assessed. Initial BTDS dosing strength, receipt of approved initial BTDS dose per the FPI, and concomitant medications were assessed in the post-index 6 month period. Results: The study included 10, 457 patients newly treated with BTDS. The majority of patients were female (69.9%) with a mean (±SD) age of 54.5 (±15.2) years. Within the 6 months prior to the index BTDS prescription, 91.7% of the patients used opioids. Overall, 48.9% of patients were prescribed the FPI approved BTDS dose. When stratified, 73.5% of opioid-naïve patients received the FPI approved initial dose compared to 46.0% of those with prior opioid experience of ≤80 mg morphine-equivalent daily dose. Patients on BTDS alone (i.e. monotherapy) had a higher rate of receiving the FPI approved initial BTDS dose compared to patients on BTDS concomitant regimens (p < 0.05). Conclusions: Practitioners demonstrated that they prescribe in accordance with BTDS's prescribing information in the majority of opioid-naïve patients and in approximately half of opioid-experienced patients. The initial opioid dose is a critical step in treatment, setting the stage for preventing side-effects and improving treatment effectiveness. Understanding practitioner prescribing practices with regard to the initial dose selection of BTDS may provide insight on how to improve outcomes of care and reduce healthcare resource utilization and costs associated with pain management. Limitations: Data obtained from prescription claims reflect only the activities of prescriptions filled, not medication use or other clinical characteristics observed by physicians when treating patients.